The impact of intention to use on Loyalty of E banking users : A UTAUT2 perspective (International Journal of Food and Nutritional Sciences, 2022)
E-banking has revolutionised the banking industry, offering increased accessibility, convenience andefficiency to users while also enhancing security measures to safe guard sensitive financialinformation. Venkatesh et al (2012) seven constructs were used. Of 7 UTAUT2 constructs firstly,facilitating condition which is the customer belief that the use of E- banking technology facilitate him/ her to do the banking transaction with enjoyment and provides benefit. Secondly, the habit isanother strong influencer of the behavioural intention to use online banking facility.